Kesempurnaan sebagai Orientasi Keilmuan dalam Teosofi Suhrawardi Al-Maqtul - Suryosumunar, John Abraham Ziswan; Kuswanjono, Arqom (Jurnal Filsafat "WISDOM", 2021)
Knowledge and science are central issues in epistemological debates. The paradigm of knowledge will imply on the methods and means that are used to achieve truth. The social contexts which influence the tradition of thought have also a strong impact on the construction of scientific paradigms. Different social contexts is the reason why the western and eastern scientific paradigms are considered to have different characteristics. In the tradition of eastern thought there are various opinions on scientific paradigm. One of which is from the perspective of Suhrawardi Al-Maqtul. By using the hermeneutic method, the author attempts to answer the question how is the concept of science and its characteristics from the perspective of Suhrawardi and what are the methods and the orientation of science that used by the perspective of Mazhab Al-Isyraqiyyah that Suhrawardi Al-Maqtul created.  The paper proposes that the concept of science in Suhrawardi’s thought resulted from syncretism of various previous eastern thoughts. Suhrawardi understood the plurality of methods that can be used, namely the burhani method with ratio and evidence, as well as the irfani method that comes from intuition. The method must be suitable for the objects of study, which is Suhrawardi’s, encompasses not only aspects of the physical world but also the non-physical supra-worldly. The orientation of this thought is not only to achieve the validity of knowledge but to achieve the perfection of knowledge or the transformation from the dark to the light of knowledge.